Day length modulates precocity and productivity through its effect on developmental rate in Origanum vulgare ssp. - Davidenco, Vanina; Argüello, Juan Alberto; Piccardi, Mónica Belén; Vega, Claudia Rosa Cecilia (Elsevier, 2019)
In Origanum spp. knowledge about mechanisms controlling development and growth in response to environmental factors such as temperature and photoperiod, is critical to improve management practices and varietal selection for an efficient use of natural resources. The aim of this research was to assess the influence of photoperiod on development, biomass and essential oil productivity in two subspecies of O. vulgare (ssp. vulgare and hirtum). For this purpose, photoperiod during vegetative phenophases up to the flowering stage (R6) was artificially extended in 6 hday−1. Extended photoperiod accelerated development and floral initiation but a genotype*photoperiod effect was found (hirtum > vulgare). Shorter cycle duration to R6 under extended photoperiod increased node differentiation, but decreased stem length and consequently stems biomass, being these effects more accentuated in O. vulgare. Essential oil productivity was always higher in O. vulgare subspecies and under the extended photoperiod treatments. Both subspecies showed a greater proportion of sabinene hydrate and thymol when day length was increased. In Origanum, thermal time to floral initiation and flowering was dependent on photoperiod with a direct consequence on cycle length, biomass accumulation and essential oil composition. This first approach to analyse the photoperiodic response of Origanum can contribute to a better understanding of the environmental and genetic regulation of growth and yield.